Autonomia e saúde mental: o desafio para uma velhice bem-sucedida - Silva, Maria Josefina da (2001)
As a result of the increase in the tiumbcr of elderly peoplc worldwide, which is regarded by some researchcrs as an irreversible process, the study of aging is in the limclight. Nursing lias clients in this age range who require specific care; therefore, it inust study such phenomenon not only in the aspects that are more closelv related to healthcare, but with an interdisciplinary and multifactonal approach. This study focuses on tlie coping mechanisms elaborated by autonomous elderh persons over their lifetime in order to solve everyday conflicts so as to preserve their mental health. Its specific objectives are: to lcam about elements in the elderly’s personal lives and family relationships that have contributed to their autonomy; to analyze the events occurring in Lhe elderly’s lives and lheir mechanisms to search for Solutions; to understand autonomy and mental health as aspects that constitute succcssful old age. Tlie research was outlined under the quahtative paradigm and used the comprchensive approach for data analysis. In order to provide support to interpretation, the theoretical tramework was based on authors that work with the themes arising from the obtained data. Tlie research site was the area of the Centerfor Family Development (Centro de Desenvolvimento Familiar- CEDEFAM), and involved the clients of Grupo I 'ida. snccessful adaptation and happy aging (adaptação bem sucedida e envelhecimento Jelitp). The life stories of six (6) elderly people, four (4) females and two (2) males, were constructcd. Ali of them participated in GRUPO VIDA. Collection and transcription of their accounts were conducted from October 1999 to April 2000 by the researcher herself the access to tlie clients took place by rneaiis of contacts widi inembers of Grupo Vida themselves. The results indicate that the interviewees had life stories which were fnll of suffering. They had faced all sorts of hardships, family abandonment and had not counted on any form of social security, except at very recent times. Autonomy was present, in various configurations, in tlie lives of the interviewees as a result of events that marked their stories, but even so they were able, in spite of everyday difficulties, to construct such autonomy. Mental health was preserved as a result of informal social support struetures, of personal support found in the faith in themselves and in sonictlnng transcendental as well as in the acceptance of events as facts, some of which offer no possibilities of intervention. Therefore, we concluded that, although more visibly experienced in adult life and especially at old age, autonomy contributes, jointly with mental health, for the interviewees to feel satisfaction in living, to cherish dreams and to fcel useful to their families and their community, which provides them with the possibility to expenence a successtul old age.